JENIS DAN MANFAAT TUMBUHAN PESISIR PANTAI KABUPATEN PADANG PARIAMAN BAGIAN SELATAN DAN KOTA PARIAMAN SUMATERA BARAT - Mella Alfianita Sari; Reki Kardiman (Universitas Cokroaminoto Palopo, 2026)
Coastal areas are ecosystems that characterized by high salinity, strong winds, and nutrient-poor soils, thus supporting only certain plant species with important ecological and economic roles. This study aimed to identify the species and utilization of coastal plants in the southern part of Padang Pariaman Regency and Pariaman City, West Sumatra. The research was conducted from September to December 2025 using a descriptive survey method through field observations, sample collection, and interviews with 60 respondents. The results showed that 24 species of coastal plants belonging to 16 families were identified, dominated by trees and shrubs. These plants are utilized as traditional medicine, food sources, building materials, household industries, tools, and ornamental plants. Cocos nucifera had the highest use value. Coastal plants play an important role in fulfilling community needs; therefore, sustainable management and conservation based on local wisdom are necessary.